Literature Review: Gender in Analytic-Behavioral Clinical Practice (Brazilian Journal of Behavioral and Cognitive Therapy, 2024)
Behavior analytic literature has traditionally been distant from gender discussions. At the same time, the researches indicate gender differences in the diagnosis and symptoms experienced by men and women concerning mental disorders. This paper presents a systematic review of the literature on behavior-analytic contributions in relation to gender variables in clinical psychology. The search was conducted between September and November of 2023 in the PsycINFO database and in national and international journals. Keywords such as "gender issues" and "behavior analytic therapy" were used. 11 articles were considered for analysis. The main themes were the intersection between feminist theories and the behavioral clinic, the gender variable in  knowledge production in the clinic context, masculinity in the clinic, and agendas of community relevance. The need to train researchers and therapists to adopt a gendered approach and to be attentive to contingencies at the cultural level in their analyses was discussed.